DEVELOPMENT OF INNOVATIVE ENTREPRENEURSHIP IN THE AGRICULTURAL SECTOR OF THE COUNTRY - Olimova Nodira Khamrakulovna; Nematova Shakhlo Egamberdievna (Galaxy International Interdisciplinary Research Journal, 2024)
The article emphasizes the importance of introducing effective socio-economic and organizational-legal mechanisms of employment based on the direct impact of agricultural development on the economic security of the country. Based on this, the paper provides conclusions and suggestions for the development of innovative entrepreneurship in this area.